A inserção do Quebec no Canadá multicultural: uma análise crítica - Dias, Bruna Alves (2023)
Canada officially adopted a multiculturalist policy in 1971. The goal was to improve the quality of intercultural relations. Two main elements of the policy were proposed as steps to achieve it: support for the maintenance and development of cultural communities and the promotion of intercultural contact along with the reduction of barriers to this participation. The introduction of this policy coincided with a shift in migration trends, where the majority of new immigrants had non-European ancestry - a precedent that has persisted since then. This dissertation focuses on an analysis of Canadian multiculturalism, both as a fact and as a state public policy. When examining the history of Canada's formation, it is possible to note that the province of Quebec emerges in this scenario as a privileged case for discussing the topic, as it is a province that has both British and French heritages and is hesitant about multicultural policies implemented in Canada. Instead, it adopts an interculturalist bias. In this context, the main objective of this dissertation is to address the multiculturalism policy adopted by Canada since 1971. Additionally, it aims to present the interculturalist model advocated by Quebec and highlight the main differences between these two models. The guiding research question is as follows: How does Quebec's intercultural approach fit into the multicultural framework of Canada? To answer it, an exploratory methodology with a qualitative approach is used, in which information will be collected from relevant bibliographical sources and official documents from Canada and Quebec, as well as from their respective government websites. In the analyzed case, it was interpreted that these are two apparently similar coexistence models but with different guidelines, in which multiculturalism is a model that focuses on managing cultural diversity, considering it a stable and defining feature of society, often represented by the metaphor of the mosaic. On the other hand, interculturality is more appropriately seen by Quebecers as a model that prioritizes integration into a shared social culture, even while recognizing distinct cultural traditions.